A befektetési termékek elemzése és a vásárlók fogyasztói magatartásának vizsgálata a Magyar Posta Zrt.-nél - Doktorné Legárt Szilvia (2018)
My objective is to assess how much the respondents know the postal investment schemes, what long term ideas they have and in which product they would be willing to invest. We may ask the question: In the current market competition, why do they choose the postal investment schemes? The Hungarian Post offers several types of investment products to serve our clients’ needs, therefore we are able to prepare a fairly extensive survey. We may achieve higher profit by creating portfolios and sales results may increase as well. Experience has shown that the respondents are willing to plan for the short term. I elaborated the topic based on secondary and primary research, I will analyse the related literature, I will evaluate data of the Central Bank of Hungary and of the Association of Hungarian Investment Fund and Asset Management Companies, as well as I will conduct questionnaire survey and in-depth interviews. I intend to present the financial and invest-ment products of Magyar Posta Zrt., which is essential to understand the topic. Another objective of my research is to – through the analysis of public data – examine the well-defined scope of clients who choose the postal investment schemes, based primarily on the decisions and strategies published by the clients themselves and the characteristics imply-ing their willingness to take risks. Based on these, conclusions may be drawn regarding the goals and behavior of the investors, which leads to the topicality of the topic through the risks which may be deduced from those. In the light of the processed studies and research it is concluded that following the economic crisis the households have produced a significant asset growth, but in order to preserve that, they avoid the risky investments. It is a potential for the Magyar Posta Zrt., but in the interest of increase of the revenues in my opinion it is necessary to promote the reliable investment products, motivate the postal employees and improve the for the cus-tomers important factors and the quality of the services (for example reduction of the awaiting- and administration time).